2022
DOI: 10.3389/fbioe.2022.1034120
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hemodynamic effects of different inferior vena cava filter heads using computational fluid dynamics

Abstract: Inferior vena cava (IVC) filters are used to prevent pulmonary embolism in patients with deep vein thrombosis for whom anticoagulation is unresponsive. The head is a necessary structure for an Inferior vena cava filter (IVCF) in clinic use. At present, there are various head configurations for IVCFs. However, the effect of head pattern on the hemodynamics of IVCF is still a matter of unclear. In this study, computational fluid dynamics is used to simulate non-Newtonian blood flows around four IVCFs with differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Therefore, in this study, in vitro measurements of the TrapEase filter in a rigid, homogeneous circular tubular IVC model derived from the study of Leask et al were used to validate the accuracy of the numerical simulations in this paper [27]. The reliability of the CFD method used in this paper has been confirmed by our previous studies [30]. The results showed that the simulated data were in high agreement with the experimental data, with an overall average deviation within 15%.…”
Section: Numerical Methods and Boundary Conditionssupporting
confidence: 55%
See 2 more Smart Citations
“…Therefore, in this study, in vitro measurements of the TrapEase filter in a rigid, homogeneous circular tubular IVC model derived from the study of Leask et al were used to validate the accuracy of the numerical simulations in this paper [27]. The reliability of the CFD method used in this paper has been confirmed by our previous studies [30]. The results showed that the simulated data were in high agreement with the experimental data, with an overall average deviation within 15%.…”
Section: Numerical Methods and Boundary Conditionssupporting
confidence: 55%
“…Compared to arteries, clinical observations show less pulsatility and pressure of IVC blood flow [10], therefore, the flow in the IVC was assumed to be constant flow [29,30] and the corresponding governing equation was the three-dimensional constant viscous incompressible Navier-Stokes equation of the following form [10,35]:…”
Section: Numerical Methods and Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The black dotted line in Fig. 9 (a) is the line where the blood flow that enters the filter interior first meets the struts and the stagnant and recirculating areas of the fully developed head region are clearly divided due to the viscous block effect [ 39 , 40 ]. This dotted line develops downwards to the inlet side (upstream of the filter) as the arm length increases.…”
Section: Resultsmentioning
confidence: 99%
“…IVCF implantation also needs to consider its ability to capture thrombi and dissolve the captured thrombi immediately, as well as the risk of IVCF displacement [14]. The performance of IVCF is closely related to hemodynamic factors [15]. Many researchers have performed numerical simulations and in vitro experiments to evaluate the culture and dissolution effects of IVCF.…”
Section: Introductionmentioning
confidence: 99%